2017
DOI: 10.5513/jcea01/18.1.1879
|View full text |Cite
|
Sign up to set email alerts
|

Mineral composition of winter oilseed rape (Brassica napus L.) seeds as a tool for oil yield prognosis

Abstract: The key objective of winter oilseed rape cultivation, resulting from its broad spectrum of uses, is to harvest maximum yield of oil. It has been formulated a hypothesis, which assumed that mineral composition of seeds allows a reliable prediction of both crude oil concentration (COC), and yield of oil (YOI). This concept has been validated in three 2007/08, 2008/09, 2009/10 seasons. The field experimental design was composed of six fertilizing treatments: absolute control (AC), NP, NPK, NPKMgS1 (1/3 total MgS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…The seeds of rape grown in the experiment were characterized by the magnesium content of 2.5 g Mg kg -1 DM. This is the value reported in a number of other studies on this issue [Korol et al 1994, Barłóg and Grzebisz 2000, Szczepaniak et al 2017.…”
Section: The Content Of Macroelements In Winter Rape Seedssupporting
confidence: 74%
“…The seeds of rape grown in the experiment were characterized by the magnesium content of 2.5 g Mg kg -1 DM. This is the value reported in a number of other studies on this issue [Korol et al 1994, Barłóg and Grzebisz 2000, Szczepaniak et al 2017.…”
Section: The Content Of Macroelements In Winter Rape Seedssupporting
confidence: 74%
“…The application of 240 kg ha −1 of N as AN resulted in a yield reduction. The observed tendencies are broadly explained by assuming an imbalance of applied nutrients or referring to the low nitrogen use efficiency (NUE) of WOSR plants [10,[45][46][47][48][49]. In the studied case, this observation was fully corroborated by the trend of partial factor productivity of N indices, which were calculated based on the N-NO 3 content in the soil at BBBCH 30.…”
Section: In-season Variability In the Growth Factor-nitrate Nitrogensupporting
confidence: 53%
“…Potassium is closely related to oil accumulation during oil seed development. For many species, Potassium fertilizer can increase the oil content (Parveen et al, 2016; Szczepaniak et al, 2017; Hu et al, 2018). The same results were verified in developmental S. tonkinensis seeds in our later research of Zhang et al Magnesium, also related to the carbohydrate metabolism and lipids synthesis (Pawar et al, 2018), showed a similar tendency with potassium, having significant positive correlations with nutrient components.…”
Section: Discussionmentioning
confidence: 99%